2018
DOI: 10.4236/gep.2018.62003
|View full text |Cite
|
Sign up to set email alerts
|

GIS Based Landslide Susceptibility Mapping with Application of Analytical Hierarchy Process in District Ghizer, Gilgit Baltistan Pakistan

Abstract: District Ghizer is a rugged mountainous territory which experiences several landslides each year. There are 16 major landslide areas and 53 villages that are at high risk to hazards. Keeping in view the severity of natural hazards, the present study was designed to generate landslide susceptibility map based on twelve causative factors viz., slope, aspect, elevation, drainage network, Stream Power Index (SPI), Topographic Wetness Index (TWI), lithological units, fault lines, rainfall, road network, land cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 24 publications
2
21
0
3
Order By: Relevance
“…The identification of previous hazards, number and types of registered losses, and damages helps to understand the kinds of hazard under record and their causes within an area of interest (Rahim et al ). For the present study, a total of 96 landslides were identified as having occurred between November 2017 and March 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of previous hazards, number and types of registered losses, and damages helps to understand the kinds of hazard under record and their causes within an area of interest (Rahim et al ). For the present study, a total of 96 landslides were identified as having occurred between November 2017 and March 2018.…”
Section: Methodsmentioning
confidence: 99%
“…This factor is another important landslide factor (Temme 2021). Lots of studies are conducted on the role of soil texture in occurrence of landslides (Lee et al 2017;Rahim et al 2018). The studies show that soils with higher silt content are more likely to erode compared to clay and sandy soils (Fonseca et al 2017).…”
Section: Soil Texturementioning
confidence: 99%
“…Phương pháp định lượng có các phương pháp thống kê như Tỷ lệ tần suất (FR), Trọng lượng bằng chứng (WOE), Hồi quy logistic (LR) và Phân tích thứ bậc (AHP). AHP là một phương pháp phân tích đa tiêu chí, một công cụ hiệu quả cho việc ra quyết định phức tạp trong nhiều lĩnh vực và đã được sử dụng rộng rãi trong việc lựa chọn các yếu tố/thành phần tác động đến trượt lở đất, là dữ liệu đầu vào để thành lập bản đồ phân vùng nguy cơ trượt lở đất trong một khu vực nghiên cứu (Ahmad, 2018;Rahim, Ali, & Aslam, 2018;Peng, Shieh, & Fan, 2012). Ở Việt Nam, trong khu vực Tây Nguyên đã thực hiện một số nghiên cứu về tai biến địa chất như X. H. Nguyen và cộng sự (2019) với đề tài "Nghiên cứu một số dạng tai biến địa chất điển hình phục vụ kinh tếxã hội Tây Nguyên" nhằm đánh giá hiện trạng bốn dạng tai biến địa chất điển hình là nứt sụt đất, trượt lở đất, lũ quét -lũ bùn đá và xói lở bờ sông; Phan và cộng sự (2016) trong đề tài "Nghiên cứu hoạt động địa động lực hiện đại khu vực Tây Nguyên phục vụ dự báo các dạng tai biên địa chất ở các vùng đập, hồ chứa và đề xuất các giải pháp phòng tránh" đã nghiên cứu làm sáng tỏ đặc điểm địa động lực hiện đại khu vực Tây Nguyên và ảnh hưởng của chúng tới đập và hồ chứa.…”
Section: Giới Thiệuunclassified